Implementasi Peningkatan Etos Kerja Islam - Muhammad As’ari Hasan (Kitabaca : Journal of Islamic Studies, 2024)
Abstract Purpose – This paper is field research entitled "Implementasi Peningkatan Etos Kerja Islam pada Koperasi Syariah Alfa Mabruk. This research is intended to answer the formulation of the problem, namely: How is the implementation of the Islamic work ethic in the Koperasi Syariah Alfa Mabruk. And what is the contribution of the Islamic work ethic in improving the performance of employees in the Koperasi Syariah Alfa Mabruk.. Design/methodology/approach - This research is a case study type research at the Alfa Mabruk Sharia Cooperative institution. Findings – The results of this study concluded that the mechanism of the Islamic work ethic in Koperasi Syariah Alfa Mabruk, started from the recruitment stage of employees, and its implementation is carried out using a structural approach and cultural approaches and reward and punishment instruments. The impact of the implementation of the Islamic work ethic on improving employee performance can be seen in improvements in employee time and discipline, improvements in attitude towards co-workers with one performance activity, friendliness towards all people both fellow employees and customers, the emergence of self-encouragement employees to continuously improve their work results.. Originality/value – the application of the Islamic work ethic to improving employee performance can be seen in improving employee time and discipline, improving attitudes towards colleagues with one performance activity.